Yellowfin Tuna Catch Demographics By Size and Sex Ratio at Bitung Ocean Fishing Port - Chris B. Sinambela; Silvester B. Pratasik; Daisy M. Makapedua; Deiske A. Sumilat; Alfret Luasunaung; Johnny Budiman; Jardie A. Andaki; Dessy A. Natalia (Sam Ratulangi University, 2025)
Yellowfin tuna is one of the most in-demand commodities for commercial exploitation due to its premium market value and nutritional content. This study examines the size structure and sex ratio of yellowfin tuna (Thunnus albacares) landed at Bitung Ocean Fishing Port. A total of 890 samples were obtained from 23 handline vessels operating in Fisheries Management Area 715 from August to October 2024. Length and weight measurements were recorded directly at the research site. The collected data were used to characterize the size structure and sex ratio. This study found a size distribution of length 96.7-163.2 cm FL and weight 13-75.9 kg. Results indicated that the predominant size class was 114.7-120.9 cm FL, comprising 279 individuals (31.35% of the sample). The sex ratio maintained a balanced 1:1 proportion, consisting of 471 males and 419 females, suggesting a healthy reproductive population structure. Keywords: size structure, length and weight measurement, sex ratio ABSTRAK Ikan tuna sirip kuning merupakan salah satu komoditi yang paling diminati untuk dieksploitasi karena memiliki harga dan kandungan gizi yang tinggi. Penelitian ini mendeskripsikan struktur ukuran dan perbandingan jenis kelamin ikan tuna sirip kuning (Thunnus albacares) yang didaratkan di Pelabuhan Perikanan Samudera Bitung. Sebanyak 890 sampel diperoleh dari 23 kapal hand line yang beroperasi di Wilayah Pengelolaan Perikanan 715 dari bulan Agustus-Oktober 2024. Data panjang dan berat ikan diperoleh langsung di lokasi penelitian. Data yang terkumpul digunakan untuk mengkarakterisasi struktur ukuran dan sex ratio. Penelitian ini menemukan sebaran ukuran panjang cagak 96,7 – 163,2 cm FL dan berat 13 – 75,9 kg. Hasil penelitian menunjukkan bahwa populasi ikan sebagian besar terdiri dari individu-individu dengan kisaran panjang 114,7-120,9 cm FL (279 individu). Perbandingan individu jantan dan betina adalah 1:1 dengan jumlah 471 individu jantan dan 419 individu betina. Kata kunci: struktur ukuran, pengukuran panjang dan berat, sex ratio